Design of Green Industry Performance Measurement and Evaluation Systems - Mubin, Ahmad; Wafa’, Qorinatul (International Journal of Sciences: Basic and Applied Research (IJSBAR), 2022)
Sustainability become the target of long-term development in national industry. One of efforts in order to sustain the industry is by applying the concept of green industry that is part of Industrial Ecology. This study aims to design system of measurement and performance evaluation of green industry. Weighting aspect and KPI (Key Performance Indicator) based on the Guidelines of Green Industry Reward from the Ministry of Republic of Indonesia. The results of the analysis of 3 aspects, namely the production process, performance of waste/emissions management, and company management, that based on the strategic objectives of each aspect, the number of KPIs is obtained in a row, namely the production process of 26 KPIs, the performance of waste/emissions management of 5 KPIs, and company management 8 KPI, so that from all aspects obtained 39 KPIs. Furthermore, each aspect and KPI is weighted as a basis for measuring and evaluating its performance.